GENETIC CHARACTERIZATION OF KISSING GOURAMI (Helostoma temminckii Cuvier, 1829) IN OGAN RIVER, SOUTH SUMATRA INFERRED FROM 16S rRNA AND COI MITOCHONDRIAL GENES - Tuty Arisuryanti; Gregorius Altius Pratama; Lukman Hakim; Johan Putra Koentjana; Fitria Kurnia Nazira (Research Center for Fisheries, 2019)
Genetic characterization data of kissing gourami are important to understand historical lineage thus enhancing sustainability of the species and to establish regulation for sustainable management of the fish stock in their habitat. However, investigation of genetic characterization of kissing gourami, one of native Indonesian freshwater fishes has poorly understood. Therefore, the aim of this study was to examine genetic characterization of the fish species collected from Ogan River, South Sumatra using partial sequences of two mitochondrial genes, 16S rRNA and COI. The results revealed that for the 621 bp determined in 16S rRNA gene of the samples, five sites were variable, of which one was parsimony informative. Concatenate data revealed three haplotypes with an overall haplotype diversity of 0.833±0.222 and nucleotide diversity of 0.003±0.001. The genetic divergence varied from 0-0.49%. Next, sequence analysis of COI gene exhibited 609 bp which can be translated into 203 amino acids. For the 609 bp sequence determined in the fish samples, three haplotypes were revealed with nine variable sites and two parsimony informatives. Haplotype diversity and nucleotide diversity of the fish samples were 0.833±0.22 and 0.00794±0.0025, respectively. The haplotype divergence between the fish samples was also supported by three nonsynonymous codons. In addition, the genetic divergence varied from 0 % to 1.16 %. The results suggest that genetic variation of the kissing gourami has to be monitored and further studies are needed to compare the same species from different location to know the historical lineage and demography.